Tantangan dan Peluang Generasi Z dalam Pengelolaan Sumber Daya Alam di Masa Depan - Adik Ayu; Neza Aini Ariyanto; Wardatun Nikmah; Nurus Sobakh (Indonesia Economic Journal, 2026)
Natural resource management is an important aspect in achieving sustainable development to ensure human welfare both in the present and future generations. Generation Z, as a digital-native generation, has significant potential in managing natural resources innovatively and adaptively. This research aims to analyze the challenges and opportunities faced by Generation Z in natural resource management. This study uses a qualitative approach using a literature review method, with data collected from books, scientific journals, and academic publications. The findings reveal that Generation Z faces several challenges, including a consumptive lifestyle and low environmental awareness. In addition, the overexploitation of natural resources remains a major problem contributing to environmental degradation. However, Generation Z also has considerable opportunities through the use of digital technology and environmental innovation. Therefore, Generation Z plays an important role as agents of change in promoting sustainable management of natural resources through technological advances and increased environmental awareness.